STRATEGI PENGEMBANGAN WISATA RELIGI BERBASIS DIGITAL DI MESJID BAITUL A’LA (GIOK) KABUPATEN NAGAN RAYA - Kurrahman, Taufit; Dimas Bagus Susanto; Ajidan (Program Studi Perbankan Syariah, Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh, 2025)
This study aims to analyze the current state of religious tourism at the Baitul A'la (Jiok) Mosque in Nagan Raya Regency and identify effective digital strategies for its development. The method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. Informants include the Department of Culture, Tourism, Youth, and Sports (DISBUDPARPORA), mosque administrators, visitors, and local traders. The results of the study indicate that the Baitul A'la Mosque has great potential as a religious tourism destination due to its unique jade architecture and high spiritual value. However, tourism management is still limited, both in terms of facilities and digital promotion. Recommended digital strategies include: (1) creation of an official website, (2) social media activation, (3) installation of a barcode of the mosque's history, (4) digitalization of local product promotion, and (5) cross-agency collaboration with digital literacy training. These findings confirm that the implementation of digital strategies not only strengthens religious appeal, but also encourages local economic growth and technology-based tourism transformation in Aceh.